2022
DOI: 10.1080/21678421.2021.2016837
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of incidence of motor neuron disease in England 1998–2019: use of three linked datasets

Abstract: Objective: This study uses three linked datasets to provide an estimate of incidence of motor neuron disease (MND) in England from 1998 to 2019. Comparison is made to previous British studies. It examines age at diagnosis and ethnicity of those affected. Methods: The literature was searched for studies of MND incidence in Great Britain from 1995 to date. The QResearch and linked Hospital Episode Statistics and Death register databases were searched from 1998 to 2019 for cases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 41 publications
1
7
0
Order By: Relevance
“…Amyotrophic lateral sclerosis (ALS) is a neurodegenerative disease typically characterized by adult-onset dysfunction of both upper and lower motor neurons (MNs). The incidence rates of this fatal disease were 1.38 (urban China), 1.5 (United States), 2.08 (Europe) per 100,000 persons ( Xu et al, 2020 ; Burchardt et al, 2022 ; Mehta et al, 2022 ), and most patients died within 3–5 years after disease onset ( Chia et al, 2018 ). No clinical therapies have been proven effective except for riluzole and edaravone, which can only delay disease progression ( Chen et al, 2016 ; Scott, 2017 ; Shefner et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Amyotrophic lateral sclerosis (ALS) is a neurodegenerative disease typically characterized by adult-onset dysfunction of both upper and lower motor neurons (MNs). The incidence rates of this fatal disease were 1.38 (urban China), 1.5 (United States), 2.08 (Europe) per 100,000 persons ( Xu et al, 2020 ; Burchardt et al, 2022 ; Mehta et al, 2022 ), and most patients died within 3–5 years after disease onset ( Chia et al, 2018 ). No clinical therapies have been proven effective except for riluzole and edaravone, which can only delay disease progression ( Chen et al, 2016 ; Scott, 2017 ; Shefner et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Motor neuron disease (MND) causes progressive neuromuscular weakness that may first present as isolated and unexplained symptoms. MND causes the deaths of 1 in 350 men and 1 in 470 women in the UK,1 although there is emerging evidence that the incidence might be higher than previously thought 2. In Europe, the annual crude incidence rate was estimated to be 2.7 per 100 000 person-years 3.…”
Section: Introductionmentioning
confidence: 98%
“…MND causes the deaths of 1 in 350 men and 1 in 470 women in the UK, 1 although there is emerging evidence that the incidence might be higher than previously thought. 2 In Europe, the annual crude incidence rate was estimated to be 2.7 per 100 000 person-years. 3 MND is difficult to recognise in primary care since it is both a relatively uncommon disease and the clinical presentations of early symptoms are sporadic and non-specific.…”
Section: Introductionmentioning
confidence: 99%
“…2 Compared to other chronic illnesses, globally motor neurone disease is relatively rare. 1,[12][13][14] A comprehensive systematic review of the literature published in 2014, comparing symptoms and prevalence of palliative carerelated problems in people living with cancer and eight non-cancer conditions, showed symptom prevalence data was the most deficient for patients with motor neurone disease. 15 Specifically, this study identified no data available regarding the prevalence of fatigue, anorexia, nausea/ vomiting, confusion/cognitive impairment, diarrhoea, social or spiritual needs for patients with motor neurone disease.…”
Section: Introductionmentioning
confidence: 99%